The Value of Health Literacy in Communication Sciences and Disorders Programs. - Brantley, Shanon Y.; McClellan, Rhonda L.; Gregg, Brent A.; Rainey, Jacquie L.; Morris, Duston D. (Perspectives of the ASHA Special Interest Groups, 2023)
Purpose: Achieving self-directed health care with good health outcomes begins with clients having adequate health literacy (HL) skills. Higher education programs, like communication sciences and disorders (CSD), have a role in cultivating HL. This study examines the speech-language pathology leaders' (administrators and faculty) sense-making of HL for their preparation programs and how/why CSD leaders implement/embed health literacy education (HLE). Method: This qualitative, phenomenological study used a screening survey of U.S. CSD leaders to assess their use of HL strategies, based on the Health Literacy Universal Precautions Toolkit-Second Edition. Ten participants who reported at least medium-frequency HL use were identified and interviewed based on the screening survey responses showing at least medium-frequency HL use. Results: CSD leaders' description and value of HL and explanations of how they implement HLE are described under three themes: HL as communicating so clients understand, HL as personal agency toward well-being, and CSD leaders waiting on others to lead HL conversations. The results indicate that most CSD leaders inaccurately perceive HL as providing health resources with clear and simple communication. Participants value HL as a step toward client empowerment. Despite CSD leaders' acknowledgment that HL holds the promise of self-directed health care, without formal conversations making sense of this significance, HLE occurs intuitively and without much depth. Conclusions: CSD leaders must understand that HL is essential for client empowerment and well-being. This unique study demonstrates that CSD leaders need to increase their knowledge of HL to ultimately help their clients achieve empowerment for optimal health outcomes.